Analisis Pengecekan Kualitas Jaringan 3G dengan Metode Short Voice Call 1 Menit dan Iterasi sebanyak 5 kali - Naufal, Daffa Dean; Saumi, Farhan; Fayakun, Kun; Ramza, Harry (PT. Riset Press International, 2024)
Third generation (3G) mobile network technology has been present for many years and has wide coverage in various regions of the world.3G network quality is often a problem faced by users.Poor network quality can cause interference in making voice calls, sending messages, and using the internet.Ensuring that the Short Voice Call method provides accurate and representative information about 3G network quality using the short voice call method for 1 minute and iterating 5 times.The results of 3G network quality measurements carried out by walk test in Batu Kuwung Room Hotel Le Dian 1st floor are as follows: out of 3 times of attempted calls made, 2 times were successful and 1 time the call was blocked. The measured RSCP has a low value with an average measured power of -110.31 dBm. The average measured Ec/No was -18.42, falling into the poor category. The SQI MOS also falls into the poor category as it has an average value of 1.96.By using the short voice call method, 3G network quality evaluation can be carried out effectively and potential problems can be identified.